Species composition, diversity and traditional uses of homegarden in Kumaun Himalaya, India - VIBHUTI, VIBHUTI; BARGALI, KIRAN; BARGALI, S S (The Indian Journal of Agricultural Sciences, 2019)
The aim of present study was to analyse the status, plant diversity and their utilization in homegardens of Kumaun Himalaya. After the recognizance survey, 12 villages were selected in Hill and Bhabhar regions and in each village10 homegardens were selected for detailed study. Out of 120 selected homegardens, 51 were large (>0.004 ha), 42 were medium (0.001-0.004 ha) and 27 were small (